Improving Students' Concept Mastery Through The Implementation of Multirepresentation-based Physics Modules. - Jannah, Ad'hani Miftachul; Mahardika, I Ketut; Supriadi, Bambang (PILLAR OF PHYSICS EDUCATION, 2025)
One of the causes of low student concept mastery is learning resources such as textbooks that are limited and less interesting to read or explore by students. Modules are one of the solutions to make it easier for students to understand physics-related concepts regarding effort and energy material. The module that will be applied to reduce these problems is a multirepresentation-based module. The purpose of this research is to analyze the improvement of students' concept mastery through the implementation of multirepresentation-based physics modules on the subject of effort and energy. The research was conducted on class X students at SMK Negeri 2 Jember with a pre-experimental, one-group pretest-posttest research design. The research sample was taken by purposive sampling using instruments such as tests, observations, interviews, and documentation. The improvement of concept mastery was measured using N-gain based on the comparison of pretest and posttest results. The results showed that the increase in concept mastery on effort and energy material was in the high category with an N-gain value of 74.72%. So, it can be concluded that the multirepresentation-based module proved effective in helping students understand physics concepts more deeply.